Comparison of the effectiveness of drills using a slide board and pull buoy on mastering freestyle swimming techniques - Muhammad Alfreda Assakha; Luqmanul Hakim (Sriwijaya Journal of Sport, 2025)
Research Problems: Fundamental skills in freestyle swimming are essential for the optimal development of swimming abilities, especially at an early age. However, many children aged 9–12 still struggle to effectively master basic techniques. Research Objectives: This study aims to compare the effect of drill methods using kickboards and pull buoys on improving fundamental freestyle swimming skills. Method: This quasi-experimental research employed a Two-Groups Pretest-Posttest Design involving 20 students from the Sai’pool Swimming Club in Cemengkalang, Sidoarjo, using matched subject ordinal pairing. Results: The t-test analysis showed a significance value of 0.000 (< 0.05), indicating a significant influence of both drill methods on enhancing basic freestyle swimming skills. Conclusion: It can be concluded that drill methods using kickboards and pull buoys are effective in improving freestyle swimming skills in children aged 9–12. This study recommends incorporating such tools into early-age swimming training programs to optimize the learning outcomes of basic techniques.